Article -Nursing models and contemporary nursing 2: can they raise standards of care?... 2 part series. - Angela Williams (Nursing Times, 2010)
This two-part series explores the value of nursing models and suggests that nurses should reconsider their use. It outlines that the fundamental concepts, beliefs, and values about nursing in these models have relevance to current policy debates about the future of nursing. The first article gave an overview of what nursing models are, how, and why they were developed, and some of the key criticisms made of them. This second article examines their relevance to contemporary nursing practice with particular reference to recent policy initiatives designed to modernise nursing and to raise standards of care.